Multimodal prehabilitation as strategy for reduction of postoperative complications after cardiac surgery: a randomised controlled trial protocol. Issue 12 (22nd December 2020) - Coca-Martinez, Miquel; Lopez-Hernandez, Antonio; Montane-Muntane, Mar; Arguis, Maria Jose; Gimeno-Santos, Elena; Navarro-Ripoll, Ricard; Perdomo, Juan; Lopez-Baamonde, Manuel; Rios, Jose; Moises, Jorge; Sanz de la Garza, Maria; Sandoval, Elena; et al.
Abstract : Introduction: Prehabilitation programmes that combine exercise training, nutritional support and emotional reinforcement (multimodal prehabilitation) have demonstrated efficacy reducing postoperative complications in the context of abdominal surgery. However, such programmes have seldom been studied in cardiac surgery, one of the surgeries associated with higher postoperative morbidity and mortality. This trial will assess the feasibility and efficacy in terms of reduction of postoperative complications and cost-effectiveness of a multimodal prehabilitation programme comparing to the standard of care in cardiac surgical patients. Methods and analysis: This is a single-centre, randomised, open-label, controlled trial with a 1:1 ratio. Consecutive 160 elective valve replacement and/or coronary revascularisation surgical patients will be randomised to either standard of care or 4–6 weeks of multimodal prehabilitation that will consist in (1) two times/week supervised endurance and strength exercise training sessions, (2) promotion of physical activity and healthy lifestyle, (3) respiratory physiotherapy, (4) nutrition counselling and supplementation if needed, and (5) weekly mindfulness sessions. Baseline, preoperative and 3-month postoperative data will be collected by an independent blinded evaluator. The primary outcome of this study will be the incidence of postoperative complications. Ethics and dissemination: This study has been approved by the Ethics Committee of Clinical investigation of Hospital Clinic de Barcelona (HCB/2017/0708). The results will be disseminated in a peer-reviewed journal. Trial registration number: NCT03466606 .